Criminal Sanctions as a Means to Eradicate Corruption Criminal Acts in Indonesia - Dahwir, Ali; Hidayah, Ardiana; Yolanda, Nina; Mukti, Zulkifli S (International Journal of Psychosocial Rehabilitation, 2020)
The criminal acts of corruption that have occurred in Indonesia have been very worrying. All the joints of the life of the nation and State have been penetrated by corrupt behavior. The perpetrators of corruption have seized the economic rights of the Indonesian people so that the State is increasingly mired in adversity. Efforts to eradicate corruption have been carried out since Indonesia's independence, but corruption is still thriving like mushrooms in the rainy season. Every time the public can see individuals caught in the act of corruption, and most of them are state officials, this causes public trust in the State to fade. Strategic efforts that can be carried out by the State are needed to eradicate corruption so that with the reduction in corruption in Indonesia, efforts to realize the ideals of a state will be easily achieved, which ultimately gives citizens equal justice and prosperity.